Fast-Velocity Eccentric Cycling Exercise Causes Greater Muscle Damage Than Slow Eccentric Cycling - Ueda, Hisashi; Tsuchiya, Yosuke; Ochi, Eisuke (Frontiers in Physiology, 2020)
This study aims to investigate muscle damage occurring in the early and recovery phases after fast-velocity and slow-velocity eccentric cycling. Eleven untrained men (age, 20.0 ± 1.7 years; height, 171.3 ± 6.8 cm; weight, 61.8 ± 7.7 kg; and %body fat, 13.2 ± 2.9%) performed slow-velocity maximal isokinetic eccentric cycling (slow-velocity; 30°/s) with one leg and fast-velocity (fast-velocity; 210°/s) isokinetic eccentric cycling with the other leg. Changes in maximal voluntary isokinetic concentric contraction (MVCC) torque at velocities of 30 and 210°/s, range of motion (ROM), and muscle soreness were assessed by pressure using a digital muscle stiffness instrument; thigh circumference, muscle echo intensity, and muscle stiffness were assessed before exercise, and immediately after exercise, 1 day, and 4 days after exercise. Comparing with the results obtained for slow-velocity cycling (post: 215.9 ± 32.3 Nm, day 1: 192.9 ± 47.4 Nm, day 4: 184.3 ± 47.2 Nm) and before exercise, MVCC after fast-velocity cycling significantly decreased at immediately (160.4 ± 43.5 Nm), 1 day (143.6 ± 54.1 Nm), and 4 days (150.1 ± 44.5 Nm) after exercise (p < 0.05). Significant increase in muscle soreness for vastus lateralis was observed after fast-velocity cycling (41.2 ± 16.9 mm) compared with slow-velocity cycling (23.7 ± 12.2 mm) 4 days after exercise (p < 0.05). However, no significant difference in muscle soreness was observed for rectus femoris and vastus medialis at any time points after exercise. In addition, no significant differences were observed in the ROM, thigh circumference, muscle echo intensity, and muscle stiffness. In conclusion, fast-velocity eccentric cycling causes a decrease in muscle strength and an increase in soreness as compared to slow-velocity eccentric cycling.